Faktor - Faktor yang Berhubungan dengan Keikutsertaan Ibu Hamil dalam Melakukan Senam Hamil pada Kelas Ibu Hamil - Maria Septiana (LPPM STIKES Al-Ma'arif Baturaja, 2020)
Pregnancy exercise is therapeutic motion exercises to prepare pregnant women, physically or mentally, to deal with the fast delivery, secure and spontaneous. The participation of pregnant women in making pregnancy exercise may be influenced by several factors such as knowledge, education, and employment of pregnant women. This study was to know the influence of knowledge, education, and employment on the participation of pregnant women for doing pregnancy exercise. This was an observational analytical study with a cross-sectional approach. The study population was 40 pregnant women. Total sampling was applied to obtain 40 samples. Bivariate analysis using the chi-square test and multivariate analysis using logistic regression was applied in the data analysis. Results of the study showed respondents have the most knowledge at 60% unfavorable category, 67.5% the level of primary education, 67.5% as many working mothers, 55% pregnant women who do not follow pregnancy exercise. There is a relationship between knowledge, education, employment with the participation of pregnant women in the class doing pregnancy exercise on pregnant women(p= 0.002, p = 0.005, p = 0.014). There are influences together knowledge (p = 0.048; Exp B = 5.196), education (p = 0.041; Exp B = 7.272) and employment (p = 0.041; Exp B = 6.201) the participation of pregnant women in doing pregnancy exercise.